2021
DOI: 10.1088/1755-1315/683/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration learning: project-based learning and local wisdom

Abstract: The application of the understanding of ecoliteracy in schools is a problem that is widely studied to make students able to live and feel the pleasure of the surrounding environment. This study aims to improve students’ understanding of ecoliteracy. This research was conducted using a medote survey of 50 elementary school students in Tasikmalaya District Indonesia. The results of the study illustrate that project-based learning in elementary schools that collaborate with the local wisdom of the Kampung Naga ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…The article on Collaboration learning: project-based learning and local wisdom, illustrates that project-based learning in elementary schools in collaboration with the local community of Kampung Naga wisdom makes learning more active, enthusiastic, and happy (Nurdiansah et al, 2021). Similar research was conducted by Retnowati et al (2020), the results showed that the development of the PjBL model based on local wisdom increased their ability to solve environmental problems, the average value of the experimental class was 0.69 and the control class was 0.055 (scale 0-1.0).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…The article on Collaboration learning: project-based learning and local wisdom, illustrates that project-based learning in elementary schools in collaboration with the local community of Kampung Naga wisdom makes learning more active, enthusiastic, and happy (Nurdiansah et al, 2021). Similar research was conducted by Retnowati et al (2020), the results showed that the development of the PjBL model based on local wisdom increased their ability to solve environmental problems, the average value of the experimental class was 0.69 and the control class was 0.055 (scale 0-1.0).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…Kelebihan model pembelajaran PjBL adalah melibatkan mahasiswa secara aktif, dapat memecahkan problem yang kompleks, dapat mengembangkan potensi diri serta mampu bekerja sama, sedangkan kekurangannya waktu yang cukup lama dalam penyelesaian suatu proyek, biaya yang mahal, kesulitan dalam pemahaman konsep (Rohana et al, 2016). Pada dasarnya pembelajaran berbasis proyek yang berkolaborasi dengan kearifan lokal telah partisipasi ekoliterasi siswa dan keaktifan (Nurdiansah et al, 2019).…”
Section: B Dokumentasi Penerapan Project Based Laerningunclassified